Spontaneous current in an holographic s+p superfluid - Arias, Raúl Eduardo (2016)
We study a Maxwell-Proca action in an asymptotically AdS black hole background. When moving the temperature of the black hole, we find rich phase diagrams that depend strongly on the dimension of the operator dual to the Proca field. We present different solutions in the bulk that correspond to the holographic dual for s-, p-, or s+p-wave superfluids. In the last case we observe the onset of a spontaneously induced current.